Prevalence and Specificity of RBC Alloantibodies in Indian Patients Attending a Tertiary Care Hospital - Shamsuz Zaman; Rahul Chaurasia; Kabita Chatterjee; Rakesh Mohan Thapliyal (Advances in Hematology)
Background. Red blood cell (RBC) alloimmunization results from genetic disparity of RBC antigens between donor and recipients. Data about alloimmunization rate in general patient population is scarce especially from resource limited countries. We undertook this study to determine prevalence and specificity of RBC alloantibodies in patients admitted in various clinical specialties at a tertiary care hospital in North India. Methods. Antibody screening was carried out in 11,235 patients on automated QWALYS 3 platform (Diagast, Loos, France). Antibody identification was carried out with an 11-cell identification panel (ID-Diapanel, Diamed GmbH, Switzerland). Results. The overall incidence of RBC alloimmunization in transfused patients was 1.4% (157/11235), with anti-E being the most common specificity (36.3%), followed by anti-D (16%), anti-c (6.4%), anti-c + E (6.4%), anti-C + D (5.1%), and anti-K (4.5%). The highest incidence of alloimmunization was observed in hematology/oncology patients (1.9%), whereas in other specialties the range was 0.7–1%. Conclusion. As alloimmunization complicates the transfusion outcomes, authors recommend pretransfusion antibody screening and issue of Rh and Kell matched blood to patients who warrant high transfusion requirements in future.